1996
DOI: 10.1037/0022-0167.43.2.131
|View full text |Cite
|
Sign up to set email alerts
|

State–Trait Anger Theory and the utility of the Trait Anger Scale.

Abstract: Eight studies present support for state-trait anger theory. In Studies 1-3, high-anger participants reported (a) greater anger in many different provocations, in their most angering ongoing situations, and in daily life, (b) greater anger-related physiological arousal, (c) greater state anger and dysfunctional coping in response to a visualized provocation, and (d) greater use of suppression and outward negative expression of anger. Only heart rate in the visualized provocation did not support predictions. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
208
2
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(245 citation statements)
references
References 45 publications
28
208
2
7
Order By: Relevance
“…Anger Anger was assessed with the State-Trait Anger Expression Inventory (STAXI; Spielberger 1996), a widely used self-report measure with sound psychometric properties (Deffenbacher et al 1996). Robust weighted least squares EFA (using polychoric correlations) indicated that the 10 items from the Trait Anger scale did not load onto a single factor (RMR=.06), which was consistent with results from other studies (e.g., Forgays et al 1997).…”
Section: Methodssupporting
confidence: 71%
“…Anger Anger was assessed with the State-Trait Anger Expression Inventory (STAXI; Spielberger 1996), a widely used self-report measure with sound psychometric properties (Deffenbacher et al 1996). Robust weighted least squares EFA (using polychoric correlations) indicated that the 10 items from the Trait Anger scale did not load onto a single factor (RMR=.06), which was consistent with results from other studies (e.g., Forgays et al 1997).…”
Section: Methodssupporting
confidence: 71%
“…The more recent STAXI-2 is a revised version of the original instrument [49]. The STAXI-2 comprises 57 items that measure both the experience and expression of anger, and studies of the measure have supported adequate discriminant and convergent validity [50]. The psychometric properties of the measure have also been supported in military samples [17], and partner-violent men score higher than nonviolent men, indicating at least adequate discriminant validity [51].…”
Section: Assessment Of Anger and Aggressionmentioning
confidence: 99%
“…La ira en conducción se ha caracterizado como un rasgo personal, específico de la situación de conducción, enmarcado dentro de la teoría de la ira estado-rasgo (Deffenbacher, Oetting, Thwaites et al, 1996) y, de forma aún más general, inserto dentro de los modelos de la interacción entre la personalidad y la situación. El interés por el estudio de la ira al conducir tiene varias razones que lo justifican.…”
Section: Introductionunclassified
“…Entre otros factores mencionados como causa de los accidentes estarían los factores de personalidad. Desde mediados de los años 90 se ha prestado gran atención a la hostilidad o ira en la conducción, sobre todo a partir del estudio original por Jerry L. Deffenbacher y colaboradores (1994).La ira en conducción se ha caracterizado como un rasgo personal, específico de la situación de conducción, enmarcado dentro de la teoría de la ira estado-rasgo (Deffenbacher, Oetting, Thwaites et al, 1996) y, de forma aún más general, inserto dentro de los modelos de la interacción entre la personalidad y la situación. El interés por el estudio de la ira al conducir tiene varias razones que lo justifican.…”
unclassified